An Examination of the Evolution of Green Industry Structure and Sustainable Cooperation Strategies Between China and the Visegrád Group: A Product Space Approach - Liping Qiu; Qianxue Chen; Xinzhe Zhu; Lihua Yang; Wenbo Gu (Systems)
The Visegrád Group (V4), as China’s key economic and trade partner in Central and Eastern Europe, plays a pivotal role in enhancing the effectiveness of sustainable development within the China-Central and Eastern Europe cooperation (China-CEEC) framework through its comprehensive green initiatives. This study analyzes export data and environmental product classifications from major countries in the CEPII-BACI database, covering the period from 2003 to 2022, to construct a green product space network. The analysis reveals the evolutionary patterns of the green industry and the collaborative transformation mechanisms between China and the V4 countries. The findings indicate the following: (1) The green product space network displays a “core-periphery” structural framework, wherein China has expanded its core product offerings by leveraging technological advancements in the photovoltaic sector, while the V4 countries enhance their resource allocation by systematically phasing out peripheral products. (2) The Green Complexity Index (GCI) suggests that China’s green production capacity has significantly improved, thereby narrowing the technological gap with Poland and Slovakia. (3) According to the Green Competition Index, a strategic complementary space exists between the two parties in the domain of medium- to high-complexity products. This study recommends extending green cooperation to higher value chain segments by establishing a collaborative innovation network for green technologies, developing a dynamic capacity optimization mechanism, and deepening the joint research and development of core products. This article offers a decision-making framework based on production capacity endowments to facilitate multinational collaborative transformations in the green industry.